Pengaruh Earning Per Share (EPS) dan Price Earning Ratio (PER) terhadap Return Saham pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia (BEI) Periode 2006-2009 - Lina Wulan Sari (Universitas Negeri Surabaya, 2018)
In particular brokerage stocks, the information has a dominant role Investors who make investments in capital market activities need different kinds of informations consists of fundamental and technical. Both this of information could be used as a basis for investors to predict the return. Information on in the financial statements consist of several financial ratios such as liquidity ratios, activity ratios, the market ratio, profitability ratios. One of the tools for predicting the stock return is the Earning Per Share (EPS) and Price Earning Ratio (PER). The population used in the study were manufacturing companies listed on in the BEI. The is year observation period is from 2006 to 2009. The analytical method used is descriptive techniques, the classic assumption test (test of multicollinearity, heteroscedasticity, autocorrelation and normality test data), multiple linear regression analysis, coefficient determination and hypothesis test. From this study, it is concluded that a simultaneously exist between the EPS and PER effects on stock returns of manufacturing firms in the BEI. Partially, influenced EPS aend PER while the stock return has effect on stock returns. Thus the only variable influencing EPS eand PER are variables that influencing to stock return. Furthermore, beside , but other than EPS aend PER, investors also need to consider other fundamental factors which are not examined in this study such as ROE, CR, PBV and others